Higher-order theories of consciousness : an anthology - Gennaro, Rocco J. (Advances in consciousness research, 2004)
Higher-Order (HO) theories of consciousness have in common the idea that what makes a mental state conscious is that it is the object of some kind of higher-order representation. This volume presents fourteen previously unpublished essays both defending and criticizing this approach to the problem of consciousness. It is the first anthology devoted entirely to HO theories of consciousness. There are several kinds of HO theory, such as the HOT (higher-order thought) and HOP (higher-order perception) models, and each is discussed and debated. Part One contains essays by authors who defend some f.